BENTUK CAYLEY COLOR DIGRAPH GRUP SIKLIK G DENGAN ORDER n - M. Ariq Zainurrifqi; Mohammad Agung; Indriati Nurul Hidayah (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2022)
Let  G be a cyclic group with set of generators . Let G with color  xi is a digraph with vertices elements of  and there is an arrow from  to  if . In this artcle, we find the Cayley color digraph of a cylic group of order . We also proved the existence of Hamiltonian cycle of the graph